Colonial origin, ethnicity, and intergeneration mobility in Africa - Patricia Funjika; Yoseph Yilma Getachew (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This paper estimates the relationship between differences in skills measured among within-country ethnic groups and individual human capital accumulation in eight African countries. Our results show that the skills of an individual in these countries depends more on the human capital levels of their parents' ethnic group (ethnic capital) than on parental investment. Therefore, differences in initial levels of ethnic capital may explain the persistence of ethnicitybased differences in educational attainment over time. Birth cohort analysis and the results from an interaction effects model show that ethnic capital has a persistent effect, and that this effect is higher in former British colonies than former French colonies. Using historical religion-based data from the colonial and independence periods as instruments for ethnic capital, we demonstrate large effects of parental ethnicity on an individual's human capital skill level and show that colonial origin may be important in understanding intergenerational mobility in African countries.
Keywords: C21; I24; J62; N37; 330; Africa; colonial origin; education; ethnicity; human capital; intergenerational mobility